Salmon P. Chase : a biography - Niven, John (Oxford University Press, 1995)
A biography of Salmon P. Chase, one of the principal political figures in the American Civil War period. A rival to Abraham Lincoln for the Republican Presidential nomination in 1860, he subsequently became Secretary of the Treasury in Lincoln's war-time cabinet.